Immune Parameters in The Prognosis and Therapy Monitoring of Cutaneous Melanoma Patients: Experience, Role, and Limitations - Neagu, Monica (Hindawi Publishing Corporation, 2013)
Cutaneous melanoma is an immune-dependent aggressive tumour. Up to our knowledge, there are no reports regarding immune parameters monitoring in longitudinal followup of melanoma patients. We report a followup for 36 months of the immune parameters of patients diagnosed in stages I–IV. The circulatory immune parameters comprised presurgery and postsurgery immune circulating peripheral cells and circulating intercommunicating cytokines. Based on our analysis, the prototype of the intratumor inflammatory infiltrate in a melanoma with good prognosis is composed of numerous T cells CD3+, few or even absent B cells CD20+, few or absent plasma cells CD138+, and present Langerhans cells CD1a+ or langerin+. Regarding circulatory immune cells, a marker that correlates with stage is CD4+/CD8+ ratio, and its decrease clearly indicates a worse prognosis of the disease. Moreover, even in advanced stages, patients that have an increased overall survival rate prove the increase of this ratio. The decrease in the circulating B lymphocytes with stage is balanced by an increase in circulating NK cells, a phenomenon observed in stage III. Out of all the tested cytokines in the followup, IL-6 level correlated with the patient's survival, while in our study, IL-8, IL-10, and IL-12 did not correlate statistically in a significant way with overall survival, or relapse-free survival.